Fiscal Surveillance in a Petro Zone : The Case of the CEMAC - Wiegand, Johannes (IMF Working Papers; Working Paper ;, 2004)
This paper discusses fiscal surveillance criteria for the countries of the Central African Monetary and Economic Union (CEMAC), most of which depend heavily on oil exports. At present, the CEMAC's macroeconomic surveillance exercise sets as fiscal target a floor on the basic budgetary balance. This appears inadequate, for at least two reasons. First, fluctuations in oil prices and, hence, oil receipts obscure the underlying fiscal stance. Second, oil resources are limited, which suggests that some of today's oil receipts should be saved to finance future consumption. The paper develops easy-to-calculate indicators that take both aspects into account. A retrospective analysis based on these alternative indicators reveals that in recent years, the CEMAC's surveillance exercise has tended to accommodate stances of fiscal policy that are at odds with sound management of oil wealth.